ESENSI PERKAWINAN DITINJAU DARI UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERKAWINAN - Firdhauzi, Salbela (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Indonesia is a country that has diverse ethnicities, religions and cultures which is referred to as a pluralistic country, so that diversity makes many differences in society so that to equalize between one ethnic group and another, uniformity of rules is needed. In marriage, special rules were created to regulate marriage as stated in Law Number 16 of 2019, because marriage is something that greatly contributes to human development on earth, so that to get to the nature of marriage there are several things that must be fulfilled. Until now marriages are often carried out without existing procedures, causing problems regarding the validity of the marriage. Because a valid marriage is a marriage that is carried out in the right way according to their respective beliefs and existing regulations. And in essence the purpose of marriage is the realization of a harmonious household and a happy family, which can be achieved by cooperation between a husband and a wife. However, over time, marital problems often arise due to several factors which eventually end in divorce so that the marriage is far from the essence of marriage itself. Community culture is also one of the things that affects the association and new habits of society, but apart from that, all that becomes an important point in marriage is the importance of understanding what the purpose and function of a marriage are, which is the main benchmark for someone to marry. This type of research is normative research that uses a conceptual approach, which means it provides a view of the legal issues or problems being studied by looking at the concepts behind the issue and research on the legal approach, this approach is by examining all the regulations in the relevant legislation. with topics that will be discussed by studying the similarities between one law and another